Antimicrobial Susceptibility Patterns of Recent Cuban Mycoplasma genitalium Isolates Determined by a Modified Cell-Culture-Based Method - Mondeja, Brian A. (PLoS One, 2016)
Isolation of Mycoplasma genitalium from clinical specimens remains difficult and few strains are available for antimicrobial susceptibility testing. We describe the antimicrobial susceptibility of M. genitalium strains grown in Vero cell culture with first- and second- line antibiotics, using a modified cell-culture-based method. Macrolide- and -fluoroquinolone resistance determinants were detected by sequencing of the 23S and parC genes, respectively. Seven strains were examined, including three new, genetically distinct M. genitalium strains isolated from endocervical and urethral swab specimens from Cuban patients together with four reference strains isolated from specimens collected from men in Denmark, Sweden and Australia. Azithromycin was the most active drug against two of the Cuban M. genitalium strains with MICs values of 0.008 mg/liter, however, one strain was macrolide resistant with an MIC of >8 mg/liter, and the A2059G resistant genotype. Ciprofloxacin was the least active antimicrobial drug and moxifloxacin was the most active fluoroquinolone against the new clinical strains, although an MIC of 1 mg/l was found for two strains. However, no relevant parC mutations were detected. MICs for tetracyclines were 0.5–4 mg/liter. Although the number of Cuban strains was low, the results suggest that a single-dose azithromycin treatment could be ineffective, and that a second-line treatment with moxifloxacin, should become an option in Cuba. To our knowledge, this is the first report of isolation and antibiotic susceptibility testing of M. genitalium strains from the Latin-American region, and the first detection of macrolide resistance in such strains.